Política de modernización de la gestión pública y calidad del servicio de autorización de radiodifusión - García Hernández, Jesús Alexis (2023)
In 2021, signs indicating a low quality of the broadcasting authorization service provided by the Dirección de Servicios de Radiodifusión (DSR) in Peru were perceived. These signs indicate a deficient implementation of the la Política de Modernización de la Gestión Pública approved by Decreto Supremo N° 004-2013-PCM. Therefore, the objective proposed was to assess the implementation of the Política de Modernización de la Gestión Pública at DSR and to verify the relationship with the quality of the service provided. A quantitative research approach (deductive) was applied, with a non-experimental design, surveying a population of 104 administrators. Problems were evidenced in all the components of the implemented Política de Modernización de la Gestión Pública (management by processes, administrative simplification and organization), with a significant and direct relationship (r = 0.77) with the perceived regular quality of the service.